Angiolymphoid hyperplasia with eosinophilia developing within a port wine stain. (15th June 2015) - Manton, Robert N.; Itinteang, Tinte; de Jong, Sophie; Brasch, Helen D.; Tan, Swee T.
Abstract : A 19‐year‐old male with a port wine stain on the base of his neck presented with a 5‐month history of gradual thickening of the involved skin which interfered with clothing and caused repeated bleeding. The lesion was excised and histopathologic examination revealed angiolymphoid hyperplasia with eosinophilia (ALHE) arising from the pre‐existing port wine stain – a rare finding with only one previously reported case. Additionally the lesion was associated with elevated serum renin levels which virtually normalized following excision of the lesion. We further demonstrated the expression of angiotensin converting enzyme and angiotensin II receptors 1 and 2 by the lesion and discuss the possible role of the renin–angiotensin system in this condition.